2013
DOI: 10.4142/jvs.2013.14.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Expression of verocytotoxicEscherichia coliantigens in tobacco seeds and evaluation of gut immunity after oral administration in mouse model

Abstract: Verocytotoxic Escherichia (E.) coli strains are responsible for swine oedema disease, which is an enterotoxaemia that causes economic losses in the pig industry. The production of a vaccine for oral administration in transgenic seeds could be an efficient system to stimulate local immunity. This study was conducted to transform tobacco plants for the seed-specific expression of antigenic proteins from a porcine verocytotoxic E. coli strain. Parameters related to an immunological response and possible adverse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
0
20
2
Order By: Relevance
“…The antimicrobial properties were evaluated against O138 E. coli, one of the major enteric pathogens of weaned piglets responsible for postweaning enteritis and enterotoxaemia that causes significant morbidity and mortality in pigs worldwide. PWD represents an important issue in swine farming that causes important economic losses, at the same time affecting the health of animals and leading to the consumption of antibiotic drugs (Rossi et al 2013). The pathogenicity is usually influenced by the presence of virulence factors, such as VT2e toxin and the F18 adhesive fimbriae (Verdonck et al 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial properties were evaluated against O138 E. coli, one of the major enteric pathogens of weaned piglets responsible for postweaning enteritis and enterotoxaemia that causes significant morbidity and mortality in pigs worldwide. PWD represents an important issue in swine farming that causes important economic losses, at the same time affecting the health of animals and leading to the consumption of antibiotic drugs (Rossi et al 2013). The pathogenicity is usually influenced by the presence of virulence factors, such as VT2e toxin and the F18 adhesive fimbriae (Verdonck et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the pathogroup of porcine verocytotoxinproducing Escherichia coli, belonging to serogroups O138, O139 and O141, is characterised by a virulence profile responsible for acute and severe enterotoxemia and for important economic losses (Verdonck et al 2002;Rossi et al 2014). Many factors, infectious and non-infectious, are involved in the outbreak of the PWD that is considered a multifactorial disease where nutrition plays a pivotal role (Rossi et al 2013). The reduction of the use of antimicrobials in food-producing animals, replacing them where possible and rethinking the livestock production system, is essential for the future of animal and public health (EFSA 2012;Murphy et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, in vitro digestion models for nutrient evaluation are important for studying both the physiology of certain segments of the digestive tract and the digestive and bioactive characteristics of tannins. In pig livestock, Enterotoxigenic E. coli (ETEC) is the most important pathotype causing both neonatal and post-weaning diarrhea (PWD), which are responsible for significant economic losses worldwide and are the most common reason for the prescription of antimicrobials in intensive systems [11,12]. The proliferation of ETEC strains in the gut and their pathogenicity can be influenced by the expression of fimbrial adhesins, which bind to specific receptor sites on small intestinal enterocytes enabling the bacteria to colonize the small intestine [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (2019) reported higher average concentration of Zn and Cu in swine manure compared to cattle and sheep manure in China (1313.00, 514.70 mg/kg, respectively). Through the manure, a large number of metallic ions can be absorbed into the soil, thus interfering with the quality of cultivation or increasing soil pollution (Lopez-Alonso et al 2012;Jakubus et al 2013;Rossi et al 2013;Rossi, Dell'Orto et al 2014a;Gul et al 2015;Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%